Role of Self-Help Groups on the Psycho-Socio-Economic Empowerment of Rural Women in Bungokho Sub County, Mbale District - Angella Gimono (Uganda Christian University, 2024)
This research aimed to investigate the role of self-help groups in the psycho-socio-economic empowerment of women in Bungokho Sub-County, Mbale District. Specific objectives included exploring existing self-help groups, examining the psycho-socio-economic empowerment experienced by women through these groups, and identifying factors hindering women's empowerment. The study involved 20 respondents selected through purposive and simple random sampling from a population of 25 participants. Findings indicated that self-help groups played a significant role in enhancing the psycho-socio-economic well-being of women in the area. However, various challenges were identified, including limited access to resources and social constraints. Recommendations include improving access to resources for self-help groups and addressing societal barriers to women's empowerment. This study contributes to the understanding of the effectiveness of self-help groups in promoting women's empowerment in rural communities.
Undergraduate Research